Male Infertility A Complete Guide to Lifestyle and Environmental Factors - du Plessis, Stefan S.; Agarwal, Ashok; Sabanegh, Jr., Edmund S. (Springer New York : Imprint: Springer, 2014)
This unique text provides a comprehensive yet concise review of the various environmental factors and lifestyle choices which impact male fertility, with special emphasis on the mechanisms that contribute to decreased sperm production and impaired function. Internationally recognized scientists and clinicians, leaders in the field of male infertility, gather their insights and discuss how to prevent, address, and treat male infertility caused by factors such as smoking, alcohol consumption, medication and drug use, obesity, dietary and exercise habits, sexually transmitted infections, psychological stress, and occupational exposure to chemicals and radiation. Written in an easy to follow, informal yet scientific style, Male Infertility: A Complete Guide to Lifestyle and Environmental Factors offers invaluable clinical guidelines for physicians and infertility experts as well as new data and research of great interest to basic scientists, andrologists, and embryologists.